1980
DOI: 10.1210/endo-106-6-1907
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Chorionic Gonadotropin and Human Luteinizing Hormone with Human Thyroid Membranes

Abstract: In an attempt to identify a possible pathogenetic role for the hCG molecule in the mechanism of the hyperthyroidism which occurs in choriocarcinoma, we have looked for evidence that the hCG molecule has a thyrotropic action on the human thyroid. The thyrotropic activity of various hCG preparations on the human thyroid was assessed by measuring the stimulation of adenylate cyclase activity in human thyroid plasma membranes purified by sucrose density gradient centrifugation. The highly purified hCG CR119 prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 25 publications
3
33
0
1
Order By: Relevance
“…The choice of a suitable animal model appeared to be difficult, because a substantial species-related variation in thyroid response to hCG is well known. Thus, intact hCG from pregnancy sources is a stimulator of significant potency in the rodent thyroid in vitro and in vivo (45)(46)(47)(48), whereas in the human thyroid it was reported to exhibit little, if any, thyrotropic activity (49)(50)(51). Moreover, desialylation and deglycosylation of hCG increase its agonistic activity measured by cAMP response in rat thyroid cells (FRTL-5) rather than transforming it into a pure antagonist like in the human thyroid (18).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of a suitable animal model appeared to be difficult, because a substantial species-related variation in thyroid response to hCG is well known. Thus, intact hCG from pregnancy sources is a stimulator of significant potency in the rodent thyroid in vitro and in vivo (45)(46)(47)(48), whereas in the human thyroid it was reported to exhibit little, if any, thyrotropic activity (49)(50)(51). Moreover, desialylation and deglycosylation of hCG increase its agonistic activity measured by cAMP response in rat thyroid cells (FRTL-5) rather than transforming it into a pure antagonist like in the human thyroid (18).…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of frank hyperthyroid ism, changes in thyroid function tests have been noted in these patients [3,4], The thyroid-stimulatory activity released from these tumours is identical to that of hCG [5]. The hormone has been shown to interact with thy roid cells in culture, competing with TSH for receptor binding sites [6] and stimulating the membrane-bound adenylate cyclase [7]. The potency of hCG as a thyroid stimulator is, however, said to be relatively low with between 10,000 and 40,000 U of hCG being equivalent to 1 mU of TSH with most in vitro assays [8][9][10], The relevance of hCG as a thyroid stimulator during normal pregnancy has, therefore, been questioned but needs to be re-examined in the light of modern thyroid function tests and bio-assay techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In early pregnan cy, several studies have shown an increase in free thyroid hormone levels as compared to nonpregnant or postpar tum controls [1][2][3][4][5][6], with a concomitant decrease in serum TSH levels [2, 3. 6-8], These results have been related to the presence of elevated hCG levels, the intrin sic thyroid stimulating activity of which has been shown by several authors in various in vivo and in vitro bioas say systems [9][10][11][12][13][14][15], However, Amir et al [16,17] did not confirm hCG thyroid stimulating activity, at least on human thyroid tissue. Other studies of thyroid function in humans showed no modifications [18][19][20] or even a decrease [21,22] in free thyroid hormone levels in the presence of decreased [20.…”
Section: Introductionmentioning
confidence: 99%